Intrinsic defence capacity and therapeutic potential of natriuretic peptides in pulmonary hypertension associated with lung fibrosis. (July 2014) - Baliga, R S; Scotton, C J; Trinder, S L; Chambers, R C; MacAllister, R J; Hobbs, A J
<x xml:space="preserve">Abstract</x> Background and Purpose Idiopathic pulmonary fibrosis (IPF) is a progressive fibro‐proliferative disorder refractory to current therapy commonly complicated by the development of pulmonary hypertension (PH); the associated morbidity and mortality are substantial. Natriuretic peptides possess vasodilator and anti‐fibrotic actions, and pharmacological augmentation of their bioactivity ameliorates renal and myocardial fibrosis. Here, we investigated whether natriuretic peptides possess an intrinsic cytoprotective function preventing the development of pulmonary fibrosis and associated PH, and whether therapeutics targeting natriuretic peptide signalling demonstrate efficacy in this life‐threatening disorder. Experimental Approach Pulmonary haemodynamics, right ventricular function and markers of lung fibrosis were determined in wild‐type (WT) and natriuretic peptide receptor (NPR)‐A knockout (KO) mice exposed to bleomycin (1 mg·kg−1). Human myofibroblast differentiation was studied in vitro. Key Results Exacerbated cardiac, vascular and fibrotic pathology was observed in NPR‐A KO animals, compared with WT mice, exposed to bleomycin. Treatment with a drug combination that raised circulating natriuretic peptide levels (ecadotril) and potentiated natriuretic peptide‐dependent signalling (sildenafil) reduced indices of disease progression, whether administered prophylactically or to animals with established lung disease. This positive pharmacodynamic effect was diminished in NPR‐A KO mice. Atrial natriuretic peptide and sildenafil synergistically reduced TGFβ‐induced human myofibroblast differentiation, a key driver of remodelling in IPF patients. Conclusions and Implications These data highlight an endogenous host‐defence capacity of natriuretic peptides in lung fibrosis and PH. A combination of ecadotril and sildenafil reversed the pulmonary haemodynamic aberrations and remodelling that characterize the disease, advocating therapeutic manipulation of natriuretic peptide bioactivity in patients with IPF.